2015
DOI: 10.1002/cne.23714
|View full text |Cite
|
Sign up to set email alerts
|

Dendrodendritic synapses in the mouse olfactory bulb external plexiform layer

Abstract: Odor information relayed by olfactory bulb projection neurons, mitral and tufted cells (M/T), is modulated by pairs of reciprocal dendrodendritic synaptic circuits in the external plexiform layer (EPL). Interneurons, which are accounted for largely by granule cells, receive depolarizing input from M/T dendrites and in turn inhibit current spread in M/T dendrites via hyperpolarizing reciprocal dendrodendritic synapses. Because the location of dendrodendritic synapses may significantly affect the cascade of odor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 82 publications
3
33
2
Order By: Relevance
“…In contrast, we found no evidence that GCs concentrate their GABAergic output to specific subregions of the MC/TC lateral dendrite (e.g., near-somatic versus distal) in contrast to a previous report (Bartel et al, 2015), and we found no difference in dynamics in different compartments. Nonetheless, our spatially restricted analysis cannot rule out higher-order patterning of turnover, such as clustered turnover dynamics and intermittent turnover at the same location, as described in mouse cortex (Chen et al, 2012; Villa et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, we found no evidence that GCs concentrate their GABAergic output to specific subregions of the MC/TC lateral dendrite (e.g., near-somatic versus distal) in contrast to a previous report (Bartel et al, 2015), and we found no difference in dynamics in different compartments. Nonetheless, our spatially restricted analysis cannot rule out higher-order patterning of turnover, such as clustered turnover dynamics and intermittent turnover at the same location, as described in mouse cortex (Chen et al, 2012; Villa et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…; Isaacson and Strowbridge, ; Bartel et al . ). However, defining excitatory dendrodendritic synapses as reciprocal is difficult because vesicles are not clustered around discrete active zones and, instead, are dispersed along the dendrite (Pinching and Powell, a ).…”
Section: Discussionmentioning
confidence: 97%
“…) mice were on a mixed C57Bl6/CBA background, which did not alter the physiological or morphological properties of neurons within the olfactory bulb (Bartel et al . ). Thus, experiments from both genetic backgrounds were grouped, where appropriate.…”
Section: Methodsmentioning
confidence: 97%
“…Lateral inhibition in olfaction has been described in previous studies [8] [9] [57] [58] [59] [60]. Similar to amplification of tactile sensations of the integumentary system, smell is enhanced by lateral inhibition.…”
Section: Lateral Inhibition In Olfactionmentioning
confidence: 75%